2021
DOI: 10.1177/03000605211039564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a blood flow restriction exercise under different pressures on testosterone, growth hormone, and insulin-like growth factor levels

Abstract: Objective To investigate the changes in serum growth hormone (GH), testosterone, and insulin-like growth factor 1 (IGF-1) during low-intensity resistance exercise under different cuff pressures. Methods We performed a single-blind, cross-over design study. Twenty-five healthy young men performed three exercise protocols as follows: 1) no blood flow restriction exercise (control group), 2) resistance exercise at 40% of arterial occlusion pressure (AOP) (low group), and 3) resistance exercise at 70% of AOP (high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
2
26
2
Order By: Relevance
“…Cortisol decreased from week 1 to week 6 in all groups, which also was not explained by plasma volume changes. Our findings agree with previous studies documenting increases in testosterone ( Madarame et al, 2010 ; Yinghao et al, 2021 ) and IGF-1 ( Takano et al, 2005 ; Madarame et al, 2010 ; Yinghao et al, 2021 ) and no change in cortisol ( Patterson et al, 2013 ) in response to a single bout of BFR resistance exercise. Few studies have examined the endocrine adaptations to BFR resistance training programs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Cortisol decreased from week 1 to week 6 in all groups, which also was not explained by plasma volume changes. Our findings agree with previous studies documenting increases in testosterone ( Madarame et al, 2010 ; Yinghao et al, 2021 ) and IGF-1 ( Takano et al, 2005 ; Madarame et al, 2010 ; Yinghao et al, 2021 ) and no change in cortisol ( Patterson et al, 2013 ) in response to a single bout of BFR resistance exercise. Few studies have examined the endocrine adaptations to BFR resistance training programs.…”
Section: Discussionsupporting
confidence: 93%
“…Possible mechanisms for the adaptations that occur with BFR exercise include enhanced metabolic stress resulting from the accumulation of metabolic by-products in the occluded limbs affecting fast-twitch motor unit recruitment and the secretion of hormones and factors that promote protein synthesis and angiogenesis ( Takarada et al, 2000 ; Suga et al, 2012 ; Karabulut et al, 2014 ). Acute bouts of BFR resistance exercise stimulate increases in blood lactate and anabolic hormones (e.g., growth hormone, testosterone, insulin-like growth factor-1, IGF-1) with minimal changes in muscle damage markers ( Takarada et al, 2000 ; Abe et al, 2005 ; Takano et al, 2005 ; Madarame et al, 2010 ; Manini et al, 2012 ; Yinghao et al, 2021 ). Another mechanism is the activation of localized chemoreceptors and exercise-induced muscle swelling, often observed following BFR exercise, that may play a role in shifting the protein balance toward anabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there was an increase in lactate concentration in all groups and an increase in GH concentration 15 min after exercise in the LL-BFR and HL groups. In fact, these findings corroborate some other studies (Kim et al, 2014;Ozaki et al, 2017;Yinghao et al, 2021), however, no association was found between the acute changes in lactate concentrations or GH and training-induced gains in muscle size and strength. Only a significant relationship was observed between changes in lactate concentrations and 1RM or the CSA in the LL group (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…The primary physiological mechanism of BFR is tissue ischemia, which results in the accumulation of byproducts and cellular swelling, leading to the release of growth factors [ 27 ]. It was shown that training with BFR substantially increases blood lactate, growth hormone, and insulin-like growth factor-1 concentrations [ 28 , 29 ], which ultimately up-regulate protein synthesis, leading to maintaining or improving muscle mass. Hence, we assumed that using BFR during FT generates further physiological adaptations in the older adult population.…”
Section: Introductionmentioning
confidence: 99%